Non-English Students’ Perception of Lecturer’s CBT (Code Mixing, Body Moving, and Translating) Strategy of English Teaching: Persepsi Mahasiswa Non-Inggris terhadap Strategi CBT (Code Mixing, Body Movements, dan Translating) Dosen dalam Pengajaran Bahasa Inggris - Arsyad Sultan, Arni (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan Colaboration with Persatuan Pranata Laboratorium Pendidikan Indonesia Tingkat Nasional, 2024)
Purpose – This inquiry attempts to investigate non-English students’ perception of lecturer’s particular strategy in English teaching namely CBT standing for code mixing, body moving, and translating. Design/methods/approach – The study is designed qualitatively. Data are collected through questionnaire by using purposive sampling. Findings – Based on the questionnaire, three findings have been resulted. Firstly, CBT strategy is necessary because students can practice their listening and speaking of certain vocabulary directly. If they hear the mixing words between English and Indonesian regularly, so it is possible for them to achieve good communication skill, and improve their knowledge of English vocabulary as well as its literal meaning. Second, CBT is important affectively because it keeps them enthusiastic in which they can imitate English pronunciation. Third, in the most effective way, non-English students prefer “complexity” in which lecturer performs word verbally and nonverbally. Lecturer says, translates, and demonstrates body language at that time lecturer says the mixing words. Research implications/limitations – This strategy could be recommended in teaching English for non-English students at basic or beginner level in school or university. However, this current research only focuses on non-English department students at this level of proficiency in which it still needs further research for the implication of CBT in intermediate and higher level or students with non-English department background. Originality/value - This research facilitates one specific strategy in English teaching for non-English students at beginner or basic level of knowledge. Abstrak Tujuan – Penelitian ini bertujuan untuk menyelidiki persepsi mahasiswa non-Inggris terhadap strategi tertentu yang digunakan dosen dalam pengajaran bahasa Inggris, yaitu CBT yang meliputi code mixing, gerakan tubuh (body moving), dan penerjemahan (translating). Desain/metode/pendekatan – Penelitian ini dirancang secara kualitatif. Data dikumpulkan melalui kuesioner dengan menggunakan teknik purposive sampling. Temuan – Berdasarkan hasil kuesioner, terdapat tiga temuan utama. Pertama, strategi CBT dianggap penting karena memungkinkan mahasiswa untuk melatih keterampilan mendengar (listening) dan berbicara (speaking) kosakata tertentu secara langsung. Dengan mendengar campuran kata antara bahasa Inggris dan bahasa Indonesia secara teratur, mereka berpotensi mencapai keterampilan komunikasi yang baik dan meningkatkan pengetahuan tentang kosakata bahasa Inggris beserta makna literalnya. Kedua, CBT dianggap penting secara afektif karena strategi ini menjaga antusiasme mahasiswa, di mana mereka dapat meniru pelafalan bahasa Inggris. Ketiga, dalam pendekatan yang paling efektif, mahasiswa non-Inggris lebih menyukai